2015
DOI: 10.1111/1467-9248.12214
|View full text |Cite
|
Sign up to set email alerts
|

Education or Personality Traits and Intelligence as Determinants of Political Knowledge?

Abstract: Recently the causal influence of education on political knowledge has been questioned. Rather, pre-adult predispositions such as personality traits and intelligence are proposed as the real causal agents. This article investigates in two studies whether education retains its explanatory power regarding political knowledge when personality traits and intelligence are taken into account. One study draws on a draftee sample and has excellent measures of both personality traits and intelligence; the other study dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…; Persson ; Rosenstone & Hansen ; Tenn ). Distinguishing between absolute motivational effects and relative resource effects of education has allowed us to engage a growing literature that has found psychological dispositions like personality traits to confound some of the educational effect on political enlightenment and engagement (Kam & Palmer ; Rasmussen , ). We argue that personal dispositions confound the motivational and cognitive effects of education but not relative resource effects.…”
Section: Discussionmentioning
confidence: 99%
“…; Persson ; Rosenstone & Hansen ; Tenn ). Distinguishing between absolute motivational effects and relative resource effects of education has allowed us to engage a growing literature that has found psychological dispositions like personality traits to confound some of the educational effect on political enlightenment and engagement (Kam & Palmer ; Rasmussen , ). We argue that personal dispositions confound the motivational and cognitive effects of education but not relative resource effects.…”
Section: Discussionmentioning
confidence: 99%
“…Education is known to be one of the strongest predictors of the level of political information/knowledge, political involvement, interest in politics, etc. (Delli Carpini and Keeter 1996;Rasmussen 2015). In other words, education indicates not only "what" individuals know about politics but also "how much and how a person thinks about politics" (Luskin 1987, 864).…”
Section: Variablesmentioning
confidence: 99%
“…Prior studies have consistently identified education as an important correlate of political knowledge (Carpini and Keeter, 1996;Nie et al, 1996;Rasmussen, 2016). Indeed, Carpini and Keeter (1996: 188) summarize their extensive study of the determinants of political knowledge as, "of all the individual demographic, structural, attitudinal, and behavioral variables we examined … education was the strongest single predictor of behavioral variables we examined … education was the strongest single predictor of political knowledge."…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Carpini and Keeter (1996: 188) summarize their extensive study of the determinants of political knowledge as: “of all the individual demographic, structural, attitudinal, and behavioral variables we examined … education was the strongest single predictor of political knowledge.” However, the interpretation of this correlation is highly debated. Some argue that education is causally prior because of its aim to develop the cognitive capacity of students, and its influence on the social networks in which one engages both during and after school (Verba et al, 1995; Carpini and Keeter, 1996; Nie et al, 1996; Rasmussen, 2016). Therefore, raising the overall level of political knowledge in the population can be achieved by increasing the overall level of education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation